OPTIMIZING THE CAPABILITIES OF TECHNOLOGY FOR LANGUAGE ACQUISITION - Numonova, Jayrona G‘olibjon qizi (Educational Research in Universal Sciences, 2024)
“Optimizing the Capabilities of Technology for Language Acquisition” delves into the burgeoning realm of technology-infused language learning, aiming to elucidate the intricate ways in which technological innovations can be leveraged to enhance and streamline the process of language acquisition. This article undertakes a comprehensive analysis of the evolving landscape of language education, encompassing the incorporation of digital platforms, adaptive learning systems, virtual reality simulations, and machine learning algorithms. By synthesizing empirical research, pedagogical frameworks, and exemplary use cases of technology in language acquisition, the article unveils the potential of technology to individualize instruction, foster authentic language immersion, and transcend conventional language learning constraints. Furthermore, the discourse encompasses considerations of equitable access, learner motivation, and the pivotal role of educators in harnessing technology to cultivate linguistic proficiency. Ultimately, it presents a compelling roadmap for educators, institutions, and policymakers to harness the transformative power of technology in nurturing multilingualism, intercultural competence, and communicative fluency in an increasingly interconnected global ecosystem.